PEDAGOGICAL PROFESSIONAL COMPETENCIES (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article covers the concept of pedagogical professional competencies, their components and their role in the modern educational process. Professional competence of a teacher is a combination of theoretical knowledge, practical skills, methodological skills, communicative potential and personal qualities of the teacher. The article analyzes general, professional, methodological, information, communication and reflexive competencies and gives an effective way of their development. In addition, the current aspects of training pedagogical personnel and their role in improving the quality of education are substantiated on the basis of a competency approach. The results of the study confirm that strengthening the professional competence of teachers is one of the main factors in modern education.